2021
DOI: 10.3324/haematol.2020.271254
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury and coronary microvascular disease in sickle cell disease

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
(14 reference statements)
0
9
0
2
Order By: Relevance
“…One hypothesis stresses the potential role of repeated microvascular ischaemic events related to sickling 8,9 . However, there is scarce evidence of microvascular myocardial injury linked to sickling in clinical studies 10 . If significant, these sickling‐induced ischaemic events should induce contractile dysfunction and an increase in the most sensitive laboratory indicators of acute myocardial ischaemia during vaso‐occlusive crises.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One hypothesis stresses the potential role of repeated microvascular ischaemic events related to sickling 8,9 . However, there is scarce evidence of microvascular myocardial injury linked to sickling in clinical studies 10 . If significant, these sickling‐induced ischaemic events should induce contractile dysfunction and an increase in the most sensitive laboratory indicators of acute myocardial ischaemia during vaso‐occlusive crises.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent retrospective study in a subset of 22 patients with SCD, Kaur et al. found that elevated troponin I predicted the presence of cardiomyopathy with a sensitivity of 88% and specificity of 57% using cardiac magnetic resonance imaging as the gold standard 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nosso grupo de pacientes classificados com escores de alto risco era relativamente baixo e esse efeito pode ter sido perdido.Seria interessante a avaliação de grupos maiores para verificar a possibilidade da utilização desse biomarcador na estimativa de gravidade. Kaur e cols255 . realizaram um estudo retrospectivo e mostraram uma correlação entre os níveis de troponina I e as alterações da perfusão miocárdica na RM.…”
unclassified
“…O corte normal foi inferior a 0,6 ng/ml. Em sete casos a troponina I foi positiva (15,9%).Nlemadim255 , estudando crianças com DF na Nigéria, encontrou elevação da troponina T em 17,6% das crianças em estado de equilíbrio. Houve detecção de Troponina T em 82,4% dos pacientes durante crise vaso-oclusiva e foi com alterações eletrocardiográficas sugestivas de isquemia miocárdica.…”
unclassified